Understanding the Status of Bilingualism among Members of Two Generations in Slovenian Istria - Kompara Lukančič, Mojca (Jezikoslovni zapiski, 2019)
The status of bilingualism in Slovenian Istria is clearly changing, which is also confirmed by the results of the general secondary-school leaving exam in Italian, the views of Italian language teachers, and the results of studies conducted in previous years. This article examines the status of bilingualism in two generations (i.e., under twenty and over forty) and defines it based on research findings.